Socio-economic determinants for poverty reduction : the case of Fiji : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Economics at Massey University - Xing, Zhongwei (Massey University, 2010)
Poverty is a multi-dimensional issue, which encompasses different dimensions of deprivation that relate to human capabilities including food security, health, education, rights, voice, security, dignity, income and consumption. Above all, poverty is denial of human rights (United Nations, 2009). Despite Fiji's as a most developed island economy, and plays an affluent role among the Pacific Island nations, its history of coups and vulnerability to external shocks have created major obstacles to reducing poverty by half by 2015. The study demonstrates that knowledge on the characteristics of the poor is vital not only because it is essential to tackle the roots of poverty but also shape the policies and strategies to reducing poverty. The study found that, in particular, the households headed by females and people with disability are most prone to poverty. Rural households are more likely subjected to poverty than urban households. The Indo-Fijian households face greater income inequalities than Fijian households, and the urban households endure greater inequalities in comparison to rural households. Being educated and employed are the key fundamental elements in reducing the likelihood of remaining poor. The study shows that people from the lowest income to the highest income groups all benefit from formal education, but it is tertiary education which has the ability to sustainably prevent people falling into poverty when the unseen event occur in the future. Also, employment in manufacturing, construction, trade and services, transportation and communications sectors are all vital determinants of poverty reduction. In particular, the manufacturing sector helps rural households in increasing the possibility of meeting the basic needs, while the transportation and communication sector helps urban households to increase the probability of meeting their basic needs. The research findings suggest that poverty reduction polices and programmes should focus on the core areas of integration and targeting, promotion of human assets, provide resources and transportation linkages for rural and urban activities, promotion of income-job-creation and income redistribution. Releasing land for commercial agriculture farming could contribute to poverty reduction in rural areas and its linkages in the urban sector could also reduce poverty in urban areas.
Keywords: Poverty -- Fiji; Economic development; Economic conditions; Social conditions